2020
DOI: 10.1177/1206331220944063
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Imageability of Port Cities Through the Visibility of Public Spaces: The Cases of Famagusta and Limassol

Abstract: Characteristics of port cities are significantly different than inland cities since they have a spatial relation with water. Waterfronts, main urban squares, and major streets are specified as the predominant components affecting socio-spatial configurations. The research assumes that the imageability of port cities, which refers to “port city identity” in this research, is associated with the visibility of these key public spaces. The port cities of Famagusta and Limassol—the current major port cities of div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…They can recognize places, use landmarks, show points of interest on the map, understand size differences, compare distances, orient themselves and recognize symbols that represent real objects [37]. Studies have shown that children are more familiar with their narrow environment (neighbourhood), and are able to recognize important city attractions [38]. Large-scale maps are of greater interest to pupils and teachers, and can incorporate other subjects into teaching.…”
Section: Geography and Spatial Skills In Kindergartenmentioning
confidence: 99%
“…They can recognize places, use landmarks, show points of interest on the map, understand size differences, compare distances, orient themselves and recognize symbols that represent real objects [37]. Studies have shown that children are more familiar with their narrow environment (neighbourhood), and are able to recognize important city attractions [38]. Large-scale maps are of greater interest to pupils and teachers, and can incorporate other subjects into teaching.…”
Section: Geography and Spatial Skills In Kindergartenmentioning
confidence: 99%